Political Institutions, Inequality, and Agricultural Growth : The Public Expenditure Connection - Allcott, Hunt; Lederman, Daniel; López, Ramón (World Bank, Washington, DC, 2012)
This paper brings together the literatures on the political economy of public expenditures and the determinants of economic growth. Based on a new dataset of rural public expenditures in a panel of Latin American economies, the econometric evidence suggests that non-social subsidies reduce agricultural GDP. Furthermore, the evidence suggests that political and institutional factors as well as income inequality are determinants of the size and structure of rural public expenditures, through which they have large and significant effects on agricultural GDP.